PENDIDIKAN KARAKTER MANDIRI SISWA MI BAIQUNIYYAH DAN ANAK BINAAN RSB DIPONEGORO - Ranti Safi’ah; Marhumah (Prodi PGMI STPI Bina Insan Mulia Yogyakarta, 2018)
This study aims to describe character education as well as the similarities and differences in the independence of MI Baiquniyyah Bantul students and children under the Diponegoro Shelter and Study Center (RSB Diponegoro). This type of research is qualitative research. Data collection techniques through observation, interviews and documentation. The results of the study: First, independent character education: (1) MI Baiquniyyah students through: Getting used to managing the distribution of snacks and lunches, taking care of prayer needs; Independence education in the learning process; reward punishment; Cheerful Saturday; The routine of PPA Baiquniyyah students. (2) RSBD Assisted Children through: Independence Training/Counseling; Counseling; Do nature activities; Eradicate the societal stigma against anjal; Restore family function; Restore the daily routine of springy; RSBD inspires through skullcap and screen printing businesses. The two similarities and differences in the independence of MI Baiquniyyah students and RSBD target children (1) The emotional independence of low-class non-boarding students and children on the street still depends on their parents, while high-class students and children of the street have good emotional independence; (2) The intellectual independence of students in grades 1 and 2 and anjal children of the street is still low, while non-school students in grades 1 and 2, students in grades 3-5 and children on the street are quite good; (3) MI Baiquniyyah students do not yet have economic independence, while anjal children on the street do economic activities to help their families while children of the street type for their own needs; (4) The social independence of MI Baiquniyyah students and anjal children on the street showed good interactions, while anjal children of the street after receiving assistance at RSBD showed positive changes.